ANALISIS POLA PENYEBARAN POPULASI HEWAN PERAIRAN DI KAWASAN PESISIR PANTAI JUMIANG - Khusnul Hotimah; ilham yusa (LPPM Universitas Negeri Jakarta, 2022)
Jumiang Beach is one of the beaches on the southern coast of Pamekasan Regency, Madura. Jumiang Beach is one of the tourist destinations in the Pamekasan area with varying levels of diversity of aquatic living things. Through this ecological research, we present the pattern of population distribution in the current Jumiang Coast region with the aim of providing information related to the diversity of living things that exist in the region. The pattern of distribution is described as the condition/condition of living creatures in the region whether or not good enough in its development or that causes the level of diversity has decreased. The method used in the form of descriptive and quadrant methods by applying misneting techniques in the form of exploratory which produces data patterns of population distribution in the form of index morisita. The results of the study stated that the pattern of population distribution in the Jumiang Coast region was classified as a group with a morisita index value of more than one.